MEDIA PEMBELAJARAN BERBASIS VISUAL BERBENTUK PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN KUALITAS BELAJAR MENGAJAR DI SEKOLAH DASAR - Nugrahani, Rahina (Lembaran Ilmu Kependidikan, 2007)
The quality of education in elementary level is demanded to always be betteralong with the worldÃ¢â¬â¢s changing. Teacher as the leading role in teaching and studyingactivity is expected to be able using acceptable media to improve studentÃ¢â¬â¢s learninginterest. Visual based teaching media in game formation is one of effective alternativemedia to improve the studying quality. Children in elementary level have tendency toplay. Fun and relaxing situation will help children to increase their learning interest.There is a new paradigm recently that through playing children will be able to learnmore and their studying activity will be more effective when the situation is set to befun. The developing of this learning media in the form of snake and lader game isaimed to give discourse about alternative teavhing media for elementary level. Theusing of this alternative media is expected to improve the quality of teaching andstudying activity in elementary level.Keywords: media pembelajaran, visual, permainan, ular tangga